Social Robot, the New CEO: Revolutionize the Robotics World by Replacing the CEOs with Social Robots Using Machine Learning and Artificial Intelligence - Ganga, Shani Lillybai (Digital Repository of Theses, 2025)
The advancement in science and technology has made human life easier. Human intellect has no comparison. We have been gifted with the intelligence to think, create new ideas, and make innovative inventions. And when the right idea is implemented in the right manner using the right technology, innovations occur. The invention of social robots is one such innovation of humans, which has certainly brought a new revolution in the era of science and technology. In recent years social robots have become more and more common and we have seen their use in a range of settings including hotels, warehouses, healthcare facilities and educational institutions. The development of social robots from machines is a result of the growing intelligence and power of robots brought about by technological advancements. With advancing technology, robots have become increasingly powerful and intelligent. Today, we have social robots capable of carrying out various tasks with enhanced intelligence. While social robots have found extensive application across different sectors, their usage in executive roles has been relatively limited. This observation sparked my interest in conducting research to explore the effectiveness of social robots if they were to replace the CEO, the highestranking position in an organization. In this research work, we intend to show that if these social robots' potentials are being well used and if they are being trained in the right way, they can prove to be a boon to many organizations around the world. Through this research work, we will be studying how a social robot can be beneficial to an organization if it acquires the topmost position that is, if it takes on the role of the CEO of an organization. We will also be studying how the advancement in artificial intelligence and machine learning, can help us in building social robots that can possess the capabilities of critical thinking and decision-making like humans. This research work will enlighten the benefits and challenges associated with implementing AI-powered social robots as CEOs of an organization and their potential effects on organizational dynamics.